Scientific methodology in studying Quranic readings - Saad Khamis Mahrous, (Islamic Sciences Journal, 2024)
ABSTRACT Praise be to Allah, Lord of the Worlds, and may blessings and peace be upon our Master Muhammad, the Seal and the Trustworthy, and upon all his family and companions. As for after: In this study, I adopted the descriptive, historical, inductive approach, and used some academic and educational scientific studies as a source of information. This research aims to renew consideration of the methodology of learning and teaching and its application in the study of the Holy Qur’an and its readings. The research also seeks to clarify the methodological principles that both the teacher and the learner must possess in the process of learning the Holy Quran. One of the challenges facing us is how to connect the past with the present in a way that preserves our great Qur’anic heritage. The research seeks to identify appropriate methodological tools for learning and teaching Quranic recitations. And clarifying the basic priorities and the focus that must be present when teaching Quranic readings through skills that include (listening, orally, memorizing, speaking, reading, or writing).